(untitled) (Heritage, 2024)
The topic of this paper is the attitude of Serbian and Albanian intellectuals towards the so-called Kosovo problem. Despite the relatively widespread view that intellectuals, on one side and the other, played a decisive role in the sharpening of antagonisms between Serbs and Albanians, and the articulation of national interests on both sides, this paper defends the view that the influence of intellectuals was not decisive, and for several reasons: the approaches of Serbian and Albanian intellectuals to solving the Kosovo problem were heterogeneous, that is, based on different political positions; likewise, the influence of intellectuals on public opinion was doubly limited: by the control of the media by the regime, and the insufficient familiarity (and interest) of the general public in the intellectual elaboration of the problem; in the end, the intellectual reception of the problems in Kosovo, it turned out, was neither comprehensive enough in the majority of cases, nor did it count on the spontaneous expressions of dissatisfaction of the Albanians and Serbs from Kosovo, so in the majority of cases it was "behind the scenes".